Physicochemical Properties of Flour and Starch Obtained from Various Quinoa Varieties - Rożnowski, Jacek; Przetaczek-Rożnowska, Izabela (Właściwości fizykochemiczne mąki i skrobi otrzymanych z różnych odmian komosy, 2023)
Currently, there is a growing interest in traditional country products, particularly those with proven health benefits. The aim of this study was to describe the chemical composition and properties of flours and starches obtained from various quinoa. The examined quinoa quinoa starches contained 7-18 times less protein and 10-25 times less lipid compared to flours. The content of amylose in the starches ranged from 15.9 to 18.5%. Flour and starch samples were also analysed for their thermal properties (DSC), pasting profile (RVA) and the content of free radicals. The Ecuadorian quinoa starches had a much higher onset (51.9-53.6°C) and peak temperature (59.3-62.1°C) than the ones from Bolivian varieties (respectively 48.5-51.6°C i 56.9-59.6°C). All the quinoa starches were susceptible to the formation of free radicals (1.05-2.06 ×1019 spins/g) irrespective of their geographical origin. The properties of the others flours and starches isolated from quinoa were influenced by the geographical origin and variety of quinoa.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2023, Nr 39, s. 1-13
Keywords: quinoa; starch; electron paramagnetic resonance (EPR); rheology; retrogradation; komosa; skrobia; elektronowy rezonans paramagnetyczny (EPR); reologia; retrogradacja